Effects of core strength training on strength quality of Chinese young male field hockey players: a pilot study - Ma, Hucheng; Soh, Kim Geok; Samsudin, Shamsulariffin (Human Resources Management Academic Research Society (HRMARS), 2024)
Strength is a fundamental component of athletic performance, particularly in sports like field hockey, where physical power and stability play a critical role. However, there is limited research exploring the impact of core strength training on the strength development of youth athletes. This study investigates the effects of core strength training on the strength quality of Chinese youth field hockey players. A cluster randomised controlled trial (C-RCT) was conducted with participants aged 15 to 17, who were divided into a core strength training group (CSTG) and a control group (CTG). The intervention lasted two weeks, with assessments of strength quality conducted at baseline and post-intervention. While no significant differences were observed in overall strength levels between the groups, the experimental group demonstrated a statistically significant improvement in the SU variable compared to the control group. These findings suggest that core strength training has the potential to enhance specific aspects of strength quality in Chinese youth field hockey players and highlight the importance of integrating such training into athletic development programs for this population.